2007
DOI: 10.1021/ol063022k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of (-)-Δ9-trans-Tetrahydrocannabinol:  Stereocontrol via Mo-Catalyzed Asymmetric Allylic Alkylation Reaction

Abstract: AbstractΔ 9 -THC is synthesized in enantiomericaly pure form, where all of the stereochemistry is derived from the molybdenum catalyzed asymmetric alkylation reaction of the extremely sterically congested bis-ortho substituted cinnamyl carbonate in high regio-and enantioselectivity.(-)-Δ 9 -trans-Tetrahydrocannabinol (Δ 9 -THC) 1, isolated 1 from female Cannabis sativa L. in 1964 has been identified as the primary psychomimetic component of marijuana. It is also known to show antiemetic, antiglaucoma, and anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 16 publications
0
46
0
1
Order By: Relevance
“…Trost and Dogra [18] have shown that THC can be synthesized in enantiomerically pure form through molybdenum (Mo)-catalyzed asymmetric alkylation of a sterically congested doubly ortho-substituted entity. An important intermediate in their route was a hydroxylated dihydrocannabidiol, which presumably can be converted into CBD proper with synthetic ease.…”
mentioning
confidence: 99%
“…Trost and Dogra [18] have shown that THC can be synthesized in enantiomerically pure form through molybdenum (Mo)-catalyzed asymmetric alkylation of a sterically congested doubly ortho-substituted entity. An important intermediate in their route was a hydroxylated dihydrocannabidiol, which presumably can be converted into CBD proper with synthetic ease.…”
mentioning
confidence: 99%
“…It can be concluded that in future, the Krapcho decarboxylation will be used to synthesise futher intermediates for natural and non-natural products. This review has not discussed all the recent examples on Krapcho decarboxylation but it is worthwhile considering the articles [24][25][26] which describe the application of Krapcho decarboxylation. We hope that the present review will attract the attention of the readers who are actively engaged in organic synthesis, especially of natural products.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, these synthetic endeavors are not reflected in the broad industrial manufacture of natural products. There is at least one total synthesis for each of the plant-derived natural products approved for therapeutic use in the last thirty years, presented in Table 1, with exemplary syntheses of (+)-artemisinin (Zhu and Cook, 2012), (+)-arglabin (Kalidindi et al, 2007), (−)-cannabidiol (Petrzilka et al, 1969), capsaicin (Kaga et al, 1989), (−)-colchicine (Lee et al, 1998), dronabinol ((−)-Δ 9 -trans-tetrahydrocannabinol (THC); (Trost and Dogra, 2007)), (+)-ingenol (as described in greater detail in the next paragraphs, ingenol is chemically converted to ingenol mebutate for therapeutic supply; (Liang et al, 2012)), masoprocol (meso-nordihydroguaiaretic acid; (Gezginci and Timmermann, 2001)), omacetaxine mepesuccinate ((−)-homoharringtonine; (Eckelbarger et al, 2008)), (−)-paclitaxel (Nicolaou et al, 1994), and (−)-solamargine (Wei et al, 2011a). Also found in this list is (−)-galanthamine, which is particularly notable because it is a rather complex plant-derived compound for which an entirely chemical industrial-scale production process exists (as described in detail in the next paragraphs).…”
Section: Organic Synthesismentioning
confidence: 99%